Advances in tumor immunomodulation based on nanodrug delivery systems - Wang, Bo; Zhang, Yue; Yin, Xunzhe (Frontiers in Immunology, 2023)
Immunotherapy is a therapeutic approach that employs immunological principles and techniques to enhance and amplify the body's immune response, thereby eradicating tumor cells. Immunotherapy has demonstrated effective antitumor effects on a variety of malignant tumors. However, when applied to humans, many immunotherapy drugs fail to target lesions with precision, leading to an array of adverse immune-related reactions that profoundly limit the clinical application of immunotherapy. Nanodrug delivery systems enable the precise delivery of immunotherapeutic drugs to targeted tissues or specific immune cells, enhancing the immune antitumor effect while reducing the number of adverse reactions. A nanodrug delivery system provides a feasible strategy for activating the antitumor immune response by the following mechanisms: 1) increased targeting and uptake of vaccines by DCs, which enhances the efficacy of the immune response; 2) increased tumor cell immunogenicity; 3) regulation of TAMs and other cells by, for example, regulating the polarization of TAMs and interfering with TAN formation, and ECM remodeling by CAFs; and 4) interference with tumor immune escape signaling pathways, namely, the PD-1/PD-L1, FGL1/LAG-3 and IDO signaling pathways. This paper reviews the progress of nanodrug delivery system research with respect to tumor immunotherapy based on tumor immunomodulation over the last few years, discussing the promising future of these delivery systems under this domain.